Certification Model of Islamic Preachers in Muslim-Majority Countries: Experience from Indonesia and Malaysia - Castrawijaya, Cecep; Rahmat, Ihsan (Yayasan Darussalam Bengkulu, 2025)
In the context of the escalating threat of global radicalism, the regulation of religious discourse has emerged as a pivotal concern for Muslim-majority nations. The present article endeavors to undertake a comparative analysis of Islamic preacher certification policies in Indonesia and Malaysia. The present study aims to elucidate the fundamental discrepancies in objectives, mechanisms, and implementing authorities. An exploratory qualitative study was conducted using a literature review. A comprehensive data set was meticulously gathered from both primary and secondary sources. The primary sources encompassed government policies, fatwas, and regulations, while the secondary sources included journals, books, and think tank reports. These data were then subjected to a rigorous thematic analysis and comparative scrutiny through a comparative matrix. The findings indicate that Islamic preacher certification in Indonesia is driven by a national security agenda to counter radicalism and represents a compromise between the state and civil society organizations. In contrast, Malaysia's mandatory tauliah (Islamic preacher certification) system prioritizes the preservation of doctrinal orthodoxy and is legally enforced by religious authorities at the state level. These disparate models reflect the distinct political landscapes and state-religion relations in both countries. Implications are both models encounter substantial challenges in regulating digital da'wah that is not bound by jurisdiction, underscoring the need for further research on religious governance in the digital age. Future studies should explore the impact of preacher certification on radicalism prevention